Chemical characterization of Lippia alba essential oil: an alternative to control green molds - Glamočlija,Jasmina (2011)
The essential oil of Lippia alba is reported as an antifungal against human pathogenic microorganisms but few articles report its use as an alternative to synthetic fungicides on green mould control. The objective of this study was to determine chemical characteristics of L. alba essential oil and its antifungal activity against green molds as an alternative to synthetic fungicides. Essential oil was extracted by Clevenger hydrodistillation, characterized by GC-MS analysis, and the structure of the main compounds confirmed by ¹H and 13C-NMR spectroscopy. Microdilution assays evaluated the essential oil minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC). Commercial fungicides Ketoconazole and Bifonazole were used as control. Essential oil yield is of 0.15% and the major components are neral (33.32%) and geranial (50.94%). The L. alba essential oil has MIC of 0.300-1.250 mg/mL and MFC of 0.600-1.250 mg/mL. Ketoconazole and Bifonazole show MIC ranging from 0.025-0.500 to 0.100-0.200 mg/mL, and MFC ranging from 0.250-0.100 to 0.200-0.250 mg/mL, respectively. L. alba essential oil is classified as citral type and the results indicate that it is a potential alternative to synthetic fungicides.